Analisis Pengaruh Country of Origin dan Pengetahuan Produk Terhadap Niat Pembelian melalui Evaluasi Produk (Studi Kasus: Distributor Elektronik Maspion) - Utomo, Sulistyo Budi; Nurhayaty, Ety; Harsono, Pramudi; Susilo, Edi (Jurnal EMT KITA, 2023)
This research analyzes the impact of Country of Origin (COO) and product knowledge on purchase intentions, with product evaluation as a mediator. A case study was conducted on Maspion brand electronic products with a sample of people selected through purposive sampling. Path analysis is used to test the hypothesis. The research results show that COO has a significant positive effect on purchase intention, while product knowledge has no significant effect on purchase intention. COO also has a significant positive effect on product evaluation, while product knowledge influences product evaluation. Product reviews themselves have a significant positive impact on purchase intention. Product reviews play an important mediating role in linking COO to purchase intention, as well as linking product knowledge to purchase intention. These results highlight the important role of the COO in influencing purchase decisions, as well as demonstrating the importance of product reviews as a mediating link in the influence of these factors. The implications of this study can be used to develop marketing and branding strategies for Maspion brand electronic products.